2022
DOI: 10.3762/bjnano.13.8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial safety study of the production process of hemoglobin-based oxygen carriers

Abstract: Hemoglobin microparticles (HbMP) produced with a three-step procedure, including coprecipitation of hemoglobin with manganese carbonate, protein cross-linking, and dissolution of the carbonate template were shown to be suitable for application as artificial oxygen carriers. First preclinical safety investigations delivered promising results. Bacterial safety plays a decisive role during the production of HbMP. Therefore, the bioburden and endotoxin content of the starting materials (especially hemoglobin) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…During peptic digestion of bovine haemoglobin at a low degree of hydrolysis, Nedjar-Arroume et al identified and characterized 24 novel and remarkable antibacterial peptides 31 . Many studies reported the usage of haemoglobin with other materials in the development of several active antibacterial agents 32 34 .…”
Section: Introductionmentioning
confidence: 99%
“…During peptic digestion of bovine haemoglobin at a low degree of hydrolysis, Nedjar-Arroume et al identified and characterized 24 novel and remarkable antibacterial peptides 31 . Many studies reported the usage of haemoglobin with other materials in the development of several active antibacterial agents 32 34 .…”
Section: Introductionmentioning
confidence: 99%